Remdesivir in COVID-19: pros and cons - Rouhana El Feghali, Yara; Rabih, Layan; Abdul Khalek, Jad; Arabi, Mariam (Frontiers in Pharmacology, 2026)
BackgroundBeginning in late 2019, the COVID-19 pandemic caused by SARS-CoV-2 rapidly evolved into a global health crisis. High rates of severe illness, hospitalizations, and long-term complications highlighted an urgent need for effective therapeutic agents. This necessity drove unprecedented efforts in drug discovery and repurposing. Remdesivir, developed by Gilead Sciences in 2009, was initially designed as a broad-spectrum antiviral targeting Ebola virus disease. Following observations of broad antiviral activity against coronaviruses, remdesivir was granted Emergency Use Authorization by the FDA in May 2020 for hospitalized patients with severe COVID-19. The FDA subsequently issued full approval in October 2020, expanding remdesivir’s use to hospitalized adults and pediatric patients aged 12 years or older and weighing at least 40 kg.AimThis paper aims to assess the advantages and limitations of remdesivir in the treatment of COVID-19, drawing on evidence from clinical trials and examining its application in patients with congenital heart disease (CHD).MethodsThe literature review was conducted until September 2025 using PubMed and Google Scholar searching for recent clinical trials in addition to relevant reviews.Results and ConclusionRemdesivir has been shown to shorten recovery time and lower mortality risk, particularly in patients at an early stage of infection with mild disease severity or requiring oxygen support. Although early guidelines advised against its use in patients with severe renal impairment, subsequent studies confirmed its safety prompting an FDA label update to allow use regardless of renal function. While some trials reported limited effects, the overall body of evidence supports remdesivir’s role in improving clinical outcomes in COVID-19 treatment. In patients with CHD, the uncertain effects of both COVID-19 and remdesivir highlight a key research gap, emphasizing the need to refine existing therapies while following National Institutes of Health (NIH) treatment guidelines.